Poverty Alleviation Through Technology-Driven Increases in Crop Production by Smallholder Farmers in Dryland Areas of Sub-Saharan Africa: How Plausible Is This Theory of Change? - Harris, David; Oduol, Judith; Hughes, Karl (Frontiers in Sustainable Food Systems, 2021)
The current paradigm of agricultural research and extension in support of rural development in Sub-Saharan Africa (SSA) is to disseminate improved technologies designed to increase the generally low crop yields per hectare on individual farms. Using data from a baseline survey (n = 7,539) from a large rural development programme implemented in five countries in SSA, we calculate the increases in yield per hectare required to significantly contribute to poverty alleviation for households managing such farms. We estimate the gap between current crop productivity and the productivity required to reach a poverty line of 1.90 per capita per day adjusted for Purchasing Power Parity (PPP). We find this gap to be very large, both in percentage and absolute terms. Median additional gross crop productivity required to reach this poverty threshold was: 324/ha/year (254% increase) in Mali; 1,359/ha/year (1,157% increase) in Niger; 4,989/ha/year (665% increase) in Ethiopia; 1,742/ha/year (818% increase) in Burkina Faso; 2,893/ha/year (1,297% increase) in Kenya. The required additional productivity taking account of production costs including the opportunity cost of family labor would need to be even higher. Given that (a) values of net productivity of improved rainfed crop technologies reported in the literature rarely exceed 1,000/ha/year; and (b) the majority of arable farms in SSA are two hectares or less with increasing trends toward land fragmentation, we argue that closing the yield gap among smallholder farmers in SSA will never—alone—be sufficient to meaningfully alleviate the high levels of poverty and deprivation many currently experience.